Mengkaji Unsur Intrinsik Cerita Rara Beruk Karya Suyono Suyanto - Bili, Oci (Wacana : Majalah Ilmiah Tentang Bahasa, Sastra Dan Pembelajarannya, 2023)
Rara Beruk was born in Palar Legen Village, South Klaten region, Surakarta. His parents, Kiai Jagasura or Jagaswara, were poor villagers. Even so, Jagasura can create a peaceful, prosperous and happy household life. Jagasura and his wife did a lot of asceticism with a request that God would give them a decent life. When Jagasura's wife became pregnant, she dreamed of seeing the full moon and the sun, both of which shone brightly on the top of the mountain. He also saw rainbow rays. The three rays fought and the moonlight faded invincible, and finally turned into stars. Then, the star was rolled up by the sun. Nyai Jagasura also gave birth to a baby girl who radiated extreme beauty. The baby was named Rara Mulatsih and nicknamed Rara Beruk. The name was given to commemorate the birth of a baby who brought abundant fortune. Since the birth of Rara Beruk, Jagasura's life has improved.